Least-Squares Reverse Time Migration Using the Gradient Preconditioning Based on Transmitted Wave Energy - Xie, Chuang; Song, Peng; Li, Xishuang; Tan, Jun; Wang, Shaowen; Zhao, Bo (Frontiers in Earth Science, 2021)
A gradient preconditioning approach based on transmitted wave energy for least-squares reverse time migration (LSRTM) is proposed in this paper. The gradient is preconditioned by using the energy of ‘approximate transmission wavefield’, which is simulated and calculated based on nonreflecting acoustic equation. The proposed method can effectively avoid the huge amount of calculation and storage required by the Hessian matrix or approximated Hessian matrix, and can overcome the influence of reflected waves, multiples and other wavefields on the gradient in gradient preconditioning based on seismic wave energy (GPSWE). The results of model experiments show that the LSRTM using the gradient preconditioning based on transmitted wave energy (GPTWE) can significantly improve the imaging accuracy of deep target and accelerate the convergence rate without significantly increasing the amount of calculation in comparison with the one using GPSWE.